PEMBELAJARAN SENI TARI INOVASI MAHASISWA PRODI PGSD DALAM PANDANGAN ALIRAN DIGITALISME DAN FUTURISME : PEMBELAJARAN SENI TARI INOVASI MAHASISWA PRODI PGSD DALAM PANDANGAN ALIRAN DIGITALISME DAN FUTURISME - Yona Syaida Oktira; Ahmad Fauzan; Zelhendri Zen; Jasrial Jasrial (Cerdas Proklamator, 2026)
This study discusses two schools of thought, namely digitalism and futurism, and examines how these two schools of thought are relevant to dance education in the curriculum of the Primary School Teacher Education Program (PGSD). The purpose of this research is to examine digitalism and futurism in dance education as part of the PGSD study program curriculum, which is undergoing rapid transformation in line with the development of digital and futuristic technology. In addition, this research aims to identify the influence of digitalism and futurism on how PGSD students learn and teach dance. Digitalism as an approach utilized in the digital technology era to expand the scope, methods, and representations in dance education; futurism as an innovative art movement to incorporate the use of technology and modern dynamics as aesthetics and expression in dance education. This study uses a qualitative method with a literature review approach to understand how these two movements can enrich the aesthetics, pedagogy, and competence of students in dance education, as well as observation to explore the understanding, challenges, and potential of integrating digital technology and futuristic trends in dance education. The results of this study can provide insights for the development of dance learning methods that are more relevant to the times. This research also discusses that the digitization of dance learning can increase digital literacy, interest in learning, and pedagogical innovation, while the principles of futurism challenge classical traditions and trigger creative thinking in creating choreographic movements and performativism.